Peran Pustakawan dalam Mengembangkan Layanan Anak dan Remaja di Era Modern - Rika Jufriazia Manita (Jurnal Adabiya, 2022)
Story telling program is an activity of story telling or telling stories to users from groups of children. The purpose of story telling in the library is to attract children to want to visit the library and reduce children's desire to play using gadgets. This story telling activity has a positive impact on children's character development and improves children's ability to understand reading material. One of the things that must be prepared in organizing story telling activities is that the librarian must master story telling or story telling techniques so that children feel satisfied and want to always follow story telling activities in the library.